Analysis On Student’s Grammatical Errors In Translating At Sman 2 Bangkinang Kota - Rahmad Hambali; Wida Rianti (FKIP - Universitas Pahlawan Tuanku Tambusai, 2025)
Language is the most significant thing in human life. Using language, people can communicate and express their ideas and feeling one to another. The purpose of this research is how student’s errors grammatical in translating at SMAN 2 Bangkinang Kota. Qualitative research methods are focused on analyzing students' errors grammatical in translating. The sample in this research was class X5 students, totaling 26 people. This qualitative research focuses on analysis students' errors grammatical in translating. Researchers use tests as instruments and analyze them based on indicators in translation error. Based on the results of rater 1 and rater 2, a total error in the word choice error type there are 13 errors with a total of 8.30%, the article error type is 11 errors with a total of 7.00%, the plural word error type is 18 errors with a total of 11.45%, the type of error there were 12 errors in noun phrases with a total of 7.65%, pronouns errors were 26 errors with a total of 16.55%, participle errors were 15 errors with a total of 9.55%, tense errors were 23 errors with a total of 14.65%, passive voice errors were 19 errors with a total of 12.10%, there were 20 types of gerund errors with a total of 12.75. For the following research which wants to research translation errors grammatical to further develop this research with different methods.